Genealogi Semiotis Term Sunah Dan Bidah: Dari Syariat Hingga Ideo-Politis - Hilmy Firdausy (Jurnal Living Hadis, 2018)
This paper wants to emphasize that the ongoing debate around the term Sunnah and Bid’ah today is ideological, even political dissension. They two no longer reflect the pattern or Islamic syariah knot. Since it was mentioned by the Prophet Muhammad in his traditions, due to external encouragement and the dynamics of the problem of Muslims, this two terms have experienced an acute swelling of meaning. Based on that, through this paper I will try to track and objectify the terms of the Sunnah and Bid’ah which are already blurred and full of dust. By returning to the beginning of its appearance in the hadith, we can find the core of the real meaning of the concept of Sunnah and Bid’ah as well as the context and purpose contained in it before it is torn apart by many factors in the history of Muslim civilization.